منهج الأنبياء في تربية الأولاد من خلال دعواتهم في ضوء القرآن - Hidayatullah Ismail; Dasman Yahya; Helmi Basri (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2023)
This research deals with the statement about the approach of the Prophets, may God bless them and grant them peace, in raising children through their supplications for their offspring in the Holy Qur’an. They are the most knowledgeable of people about the methods of correct upbringing, and the most careful of people about their children and what is best for them. They, may God’s prayers be upon them, used to pray to God for their children’s righteousness before and after their birth. The research included an introduction, two sections, and a conclusion. The research aims to identify the greatest reasons for the well-being of the offspring - after taking into account the reasons - frequent supplication for them and supplication to God to rectify them, then highlighting the types of prophets’ supplications, their etiquette, and their methods of supplication. The importance of this topic is evident because supplication has a great impact on the welfare of children. We found the best of creation among the prophets and messengers asking God Almighty and urging Him, Glory be to Him, to improve their offspring. The status of the blessing of children in Islam, and the necessity of taking care of their upbringing, has become clear, and there is no clearer evidence of this than the Holy Qur’an’s explanation of the status of this divine gift. The supplication of parents for children is the approach of the prophets and the righteous among His servants.Keywords: Curriculum of the Prophets, raising children, light of the Qur’an